Wages As the Basic Element of Labor Costs in Poland - Ewa MACKOWIAK (Communications of International Proceedings, 2022)
The concept of labour costs was introduced into Polish literature by H. Halama in 1962, defining labour costs as: "the total costs incurred by an enterprise in connection with the employment of white-collar and manual workers"[1]. Jan Kordaszewski was a Polish economist who undertook research on employment costs in the early 70s. In his opinion, "labor costs - the total expenditure of a business entity, incurred for the benefit of its employees, their families and students"[2].   In turn, K. Górka and S. Chomątowski understood labor costs as a set of financial outlays and costs related to the employment of employees in a specific enterprise. A comprehensive definition was presented by J.W. Wiktor. Returned he pointed out that labor costs are an economic category that consists of wages and non-payroll costs related to the acquisition, maintenance, and the use of labor resources.[3] Higher labor costs (higher wage rates and employee benefits) make workers better off, but they can reduce companies’ profits, the number of jobs, and the hours each person works. The minimum wage, overtime pay, payroll taxes, and hiring subsidies are just a few of the policies that affect labor costs. Policies that increase labor costs can substantially affect both employment and hours, in individual companies as well as in the overall economy.[4] The aim of the article is to analyze the nature, components and level of labor costs. The article consists of two parts. The first one, based on the literature of the subject and legal acts, is focused on labour costs concepts, elements and its character. The second part identifies elements of remuneration. The research is based on analysis of data on labor costs made available by the Department of Demographic Research and Labor Market and the European Statistical Office. The paper provides analysis for Poland and EU for minimum wage, salary level in particular economy sectors and labor costs elements
Keywords: labour cost; labour cost elements; costs; level of labor costs.